2018
DOI: 10.3390/nu10010046
|View full text |Cite
|
Sign up to set email alerts
|

Desphospho-Uncarboxylated Matrix-Gla Protein Is Increased Postoperatively in Cardiovascular Risk Patients

Abstract: Background: Matrix Gla protein (MGP) is an extrahepatic protein that is dependent on glutamate carboxylation, a vitamin K-dependent process. Its dysfunctional form, desphospho-uncarboxylated-MGP, has been associated with increased arterial calcification and stiffness. The aim of this study was to measure the degree of postoperative carboxylation of MGP and two other Gla proteins in patients scheduled for abdominal or orthopaedic surgery. Methods: Forty patients undergoing abdominal or orthopaedic surgery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…This effect of vitamin K in higher dosages corroborates results from 2 recent studies [28,29]. Our dp-ucMGP levels are high, but in a previous study on postoperative changes after major surgery, even higher dp-ucMGP levels were measured on day 5 compared to day 1 after surgery [14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This effect of vitamin K in higher dosages corroborates results from 2 recent studies [28,29]. Our dp-ucMGP levels are high, but in a previous study on postoperative changes after major surgery, even higher dp-ucMGP levels were measured on day 5 compared to day 1 after surgery [14].…”
Section: Discussionsupporting
confidence: 92%
“…The delta changes between the time points also demonstrated a stronger return to a normal Owren PT in the group with increased or unchanged SOFA score. Thrombin generation assay, reagent B; 12 Thrombin generation assay, reagent C, for this analysis one sample was missing in the increased or stagnant SOFA score group, calculations are based on 24 patients for this analysis; 13 Rotational thromboelastometry; 14 Clotting time; 15 Clot formation time; 16 Maximal clot firmness; 17 Maximal lysis; 18 C-reactive protein; 19 Greater decrease in the group with decreased SOFA score.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis and data presented in this review further suggest that extrahepatic vitamin K deficiency cannot be alleviated with VK1 supplementation alone [101]. Although it remains a challenge to directly screen VK2, there is a strong argument that patients with osteoporosis, cardiovascular disease, and diabetes are deficient in VK2 [102][103][104]. The MK-7 isoform appears to have the greatest extrahepatic bioavailability [9].…”
Section: Plausible Biological Rationalementioning
confidence: 89%
“…Among 40 patients scheduled for orthopedic or abdominal surgery, serum dpucMGP levels were significantly higher in those with previous history of CVD compared to those with no record, while dpcMGP levels were not significantly different among groups. Post-operatively, only serum dpucMGP (and not dpcMGP) levels were significantly increased in the group with history of CVD [105]. A recent meta-analysis including 7 studies and 3301 patients reported that circulating inactive dpucMGP was a strong independent predictor of overall and CV mortality, but not CVD [106].…”
Section: Dpucmgp and Mortality/cv Eventsmentioning
confidence: 99%